PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN DANA DESA DI DESA MEKAR JAYA KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - RIFAYANI, DESIYANTI; TRIWAHYUNI, NADIA (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
Village funds are one of the government's efforts to realize equitable development between central and regional areas. One form of accountability in the management of village funds by the village government is through the implementation of transparency and accountability in budget utilization. This study aims to analyze the influence of transparency and accountability on the management of village funds in Mekar Jaya Village, Kampar Kiri District, Kampar Regency. In the context of village governance, transparency and accountability are key principles in achieving good governance. In recent years, the allocation of village funds has continued to increase, thus requiring their management to be carried out openly and responsibly. This research employs a quantitative approach by distributing questionnaires to village officials, community leaders, and local residents in Mekar Jaya Village. Data analysis was conducted using statistical tools to determine the effect of each variable. The results showed that partially, transparency does not have a positive effect on the management of village funds, while accountability has a positive effect. Simultaneously, transparency and accountability do not have a significant positive effect on the management of village funds.